TAEKWONDO FIGHTING AUTOMATIC SCORING SYSTEM*) - dan Muslikhin, Feris Kurniawan, M.Purbotedjo L., (Pelita - Jurnal Penelitian Mahasiswa UNY, 2008)
The aim of this research is to design an automatic scoring system in thetaekwondo champion.This research employed the model of waterfall cycle, that is (a) analysis; (b)designing module; (c) coding; (d) technique of experiment; (e) experiment of thedevice. This system is designed from the hardwares, namely, transmitter circuit,circuit, system of minimum microcontroller AT89S51, circuit of seven-segmendriver, circuit of micro switch and component of software; program writing usingnotepad, compilling program suing matrix exe, and downloading program usingaec.isp.The result of this research is the prototype of a scoring system of taekwondochampion. This system can show score in the display as the data are transmittedby transmitter and received by receiver. The output of the receiver is voltage3.8V- 4v used to trigger transistor which functions as the input microcontroller.The input data from the receiver will be procceeded by microcontroller and theoutput microcontroller will be displayed by microcontroller. The overall resultsare (a) radius of radio waves reaches 10 meters, (b) the device of automatic scoringsystem of taekwondo champion can show the result after being accumulated asreal time; (c) it is supplemented with penalty knop.Key Words: Taekwondo, scoring system